Effect evaluation of one-hop transmission distance vs performance in wireless sensor network - Zhi-jie LIU; Jun TAO; Wen-qiang CHEN (Tongxin xuebao)
The research was on the influence of transmission distance respectively on energy consumption and transmission rate in wireless sensor network.The views of traditional work on this impact was not so precise,which was essential to the performance of WSN.The sensor node used,experimental environment and design have been introduced;Then the packet loss ratio for different transmission distance have been examined experimentally,and their functional relation by fitting the experimental data have been acquired; finally,considering packet retransmission based on that conclusion at the same time,focused on the variance of energy cost and transmission rate with distance.The main contribution is to acquire the quantitative effect evaluation of one-hop transmission distance and performance in WSN.